Polymorphism of Insulin-like growth factor-I (IGF-I) gene and their effect on growth traits in Indonesia native chicken - Supriyantono, A.; Uhi, M.H. (Indonesian Journal of Animal and Veterinary Sciences, 2009)
The research was aimed is to detect Insulin-like growth factor-I (IGF-I) gene polymorphism and their effect on growth traits in Indonesia natives chicken. Seventy two Indonesian native chicken are going to be used in this research. The polymorphism of IGF-I gene was detected by PCR-RFLP/Pst-I. Four growth traits (body weight at 1, 2, 3, and 4 months) were recorded for analyzing the association between IGF-I gene polymorphism and growth performance.The results showed that allele A (621 bp) and allele B (364 and 257 bp) were found in this research. It was found that Indonesian native chicken carried high frequencies of allele A (0.82), and frequencies of IGF-I genotypes (AA, AB, BB) were 68.0, 27.8, and 4,2%, respectively. When compared to the IGF-I genotypes, the BB genotype had the highest body weight at 1, 2, 3, and 4 month (P<0.05). The results showed that the B allele was positive of associated to a higher growth rate. Therefore, these results suggest that there is a possibility of IGF-I genotypes acting as a molecular marker for growth rate of Indonesia native. Key words: Polymorphism, IGF-I, Polecular Marker, Growth, Indonesia Native